The Impact of COVID-19 Pandemic on Sustainability, Employee Retention and Innovative Performance in The Malaysian Manufacturing Industry - Ishaq Ibrahim; Walid Abdullah Al-Suraihi; Al-Hussain Abdullah Al-Suraihi; Kalsom Ali (Asian Scholars Network (ASNet), 2024)
Non-Indexed Publication